Role of NGOs on Socio-Economic Condition at Sherpur Sadar Upazila - Latif, MB; Akter, S (Journal of Environmental Science and Natural Resources, 2018)
The present study examines the impacts of NGOs activities on socio-economic environment of rural people at Sherpur Sadar, Bangladesh using purposive random sampling technique with questionnaire survey, detail interview for case study and secondary data. The main objectives of the research were- to determine the existing services of those NGOs; to assess the past and present socio-economic condition of the beneficiaries. A total of 84 beneficiaries of two villages were selected for questionnaire survey and 4 were interviewed in detail. The secondary data were collected from journal papers, articles, books, official documents, thesis papers, daily newspapers etc. In the studied two village, monthly income of the respondents was increased after taking loan from NGOs i.e. 43.20% respondent’s monthly income was between 8,000-10,000tk while it was 15.87% before taking loan and 5.95% respondents earned money above 10,000tk before taking loan but the percentage of respondent’s income was also increased (29.54%) after taking loan. J. Environ. Sci. & Natural Resources, 10(2): 79-85 2017